Factors influencing performance of dividend by Bank Rakyat / Nurull Eddaliyana Hasbullah - Hasbullah, Nurull Eddaliyana (2013)
The objective of this study is to identify some factors that influence the stability of dividends rate during 1986 until 2011 in Bank Kerjasama Rakyat Malaysia. According to Bank Rakyat annual reports on financial statements, Bank Rakyat has achieved or maintaining its dividend rate up to 30% for 26 years consecutively. Bank Rakyat has been establishing as one of the largest Islamic cooperation bank in Malaysia with the total assets of RM72.48 billion. This might give a motivation to examine the influencing factors on the performance of Bank Rakyat dividend. A regression model of multiple linear regressions used to determine the result in this study. Researcher chose dividend rate as the dependent variable while gross domestic product (GDP), bank size, liquidity and return on assets as the independent variables. These factors include the external and internal factors. In determine the bank size, it was measured by using the total assets of Bank Rakyat. For measuring the liquidity value, researcher used the formula of current assets divide by current liabilities while in measuring the value of return on assets, researcher used earning after tax divide total assets. The result indicate that Gross Domestic Product were the most significant correlations factors that contribute to the performance of bank's dividend.